2017
DOI: 10.1177/1755088217713765
|View full text |Cite
|
Sign up to set email alerts
|

The new anarchy: Globalisation and fragmentation in world politics

Abstract: Modern International Relations theory has consistently underestimated the depth of the problem of anarchy in world politics. Contemporary theories of globalisation bring this into bold relief. From this perspective, the complexity of transboundary networks and hierarchies, economic sectors, ethnic and religious ties, civil and cross-border wars, and internally disaggregated and transnationally connected state actors, leads to a complex and multidimensional restructuring of the global, the local and the uneven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 77 publications
0
21
0
1
Order By: Relevance
“…Many geopolitical changes and economic factors such as security issues or global financial crisis have affected the mutual trade between EU and main trading partners in the years 2005 -2016 (Cerny & Prichard, 2017). After recording a significant and almost continuous fall until 2011, the share of the United States in EU total trade in goods has begun to increase again reaching 17.7% in 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Many geopolitical changes and economic factors such as security issues or global financial crisis have affected the mutual trade between EU and main trading partners in the years 2005 -2016 (Cerny & Prichard, 2017). After recording a significant and almost continuous fall until 2011, the share of the United States in EU total trade in goods has begun to increase again reaching 17.7% in 2016.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of neo-medievalism has frequently been recharged to analyze, for instance, digital communication (Kobrin 1998), international law (Arend 1999), the EU-project (Brommesson 2008), civil war (Winn 2004), and global warfare (Ligouri Bunker 2016). Whereas the medieval analogy in Bull's understanding has a normative connotation, as a catalyst for functional differentiation, cooperation, and diplomacy in the international system, critical scholars have warned that this idealized understanding of the medieval order is inadequate for describing the reality of contemporary world politics (Cerny and Prichard 2017), and that it has come to enforce, as Holsinger (2007) has it, "a paradigm of neoconservative intellectual renewal." Previous research has also shown how the imagery of the Middle Ages is frequently reproduced in popular culture (De Groot 2009), and how medieval tropes are employed to animate contemporary political issues (Eco 1986;Elliott 2017;Robinson 2012).…”
Section: Anarchy and Neo-medievalismmentioning
confidence: 99%
“…Anarchy in the Game of Thrones social movement nexus (Turner 1998). In this same, explorative vein, Cerny and Prichard (2017) suggest that anarchy could be used to conceptualize "economic and political power as disaggregated and decentralized, networked and plural." Such an approach challenges Wendt's (1992) personification of state power to instead conceptualize anarchy in terms of pluralization (Prichard 2017).…”
Section: Anarchy and Neo-medievalismmentioning
confidence: 99%
“…What unites such diverse writers is the conviction that international society is animated by ‘anarchical’ freedom (see also Cerny and Prichard, 2017). This is a kind of equal freedom which translates into value pluralism.…”
Section: Conclusion: International Anarchy and The Promise Of Normatimentioning
confidence: 99%